2013
DOI: 10.1121/1.4807816
|View full text |Cite
|
Sign up to set email alerts
|

Comments on “A theoretical model of the pressure field arising from asymmetric intraglottal flows applied to a two-mass model of the vocal folds” [J. Acoust. Soc. Am. 130, 389–403 (2011)]

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The fluid solver is based on prior modeling efforts that implemented a Boundary Layer Estimation of the Asymmetric Pressures (BLEAP) to determine the effect of asymmetric fluid loading arising from glottal jet asymmetry [28]. This approach is updated to also consider the effects of flow curvature at the inlet to the glottis [29, 30]. The proposed acoustic solver is an extension of the work initially proposed by Titze [33, 34], where the primary glottal dipole source was described in the framework of a symmetric Bernoulli flow coupled with a wave reflection analog sound propagation scheme.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…The fluid solver is based on prior modeling efforts that implemented a Boundary Layer Estimation of the Asymmetric Pressures (BLEAP) to determine the effect of asymmetric fluid loading arising from glottal jet asymmetry [28]. This approach is updated to also consider the effects of flow curvature at the inlet to the glottis [29, 30]. The proposed acoustic solver is an extension of the work initially proposed by Titze [33, 34], where the primary glottal dipole source was described in the framework of a symmetric Bernoulli flow coupled with a wave reflection analog sound propagation scheme.…”
Section: Theorymentioning
confidence: 99%
“…It has been suggested that because the glottal jet asymmetrically bends towards a VF wall, lateral loads arising due to flow curvature should be considered [29, 30]. The pressure loading arising solely due to flow curvature can be computed in region (1) in Fig 1.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Through our recent numerical analysis in the simplified larynx model (Zheng et al, 2011a;Zheng et al, 2011b), we were able to attribute this jet deflection/asymmetry to the effects of the supra-glottal vortex structure rather than intrinsic intra-glottal "Coanda effects." However, it should be pointed out that the actual link between jet deflection and sound production is still debated (Erath et al, 2011;Hirschberg, 2013).…”
Section: Dynamics Of the Glottal Jetmentioning
confidence: 99%